2022
DOI: 10.20527/ht.v5i1.5156
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Tingkat Pendidikan dan Pekerjaan dengan Kejadian Covid-19 di Puskemas Pemurus Dalam Kota Banjarmasin

Abstract: The incidence of COVID-19 continues to increase, especially in the city of Banjarmasin. The increasing number of cases of COVID-19 is caused by several factors, including sociodemographic risk factors such as level of education and occupation. This study aims to analyze the relationship between education and employment levels with the incidence of COVID-19 at the Pemurus Dalam Health Center in Banjarmasin City. The research method is analytic observational with a case control approach. Sampling using simple ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(11 reference statements)
0
0
0
2
Order By: Relevance
“…Jenis pekerjaan terbanyak yang didapatkan adalah pegawai yaitu 12,6%. Hasil yang didapatkan dari penelitian ini sesuai dengan penelitian yang dilakukan oleh (Rahman et al, 2022) dimana jenis pekerjaan sebagai karyawan memiliki proporsi tertinggi yaitu 40,62%. Hal ini dapat dikarenakan karyawan yang tidak melakukan work from home (WFH) seperti tenaga kesehatan, pengemudi ojek online lebih mudah terpapar akan infeksi COVID-19.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Jenis pekerjaan terbanyak yang didapatkan adalah pegawai yaitu 12,6%. Hasil yang didapatkan dari penelitian ini sesuai dengan penelitian yang dilakukan oleh (Rahman et al, 2022) dimana jenis pekerjaan sebagai karyawan memiliki proporsi tertinggi yaitu 40,62%. Hal ini dapat dikarenakan karyawan yang tidak melakukan work from home (WFH) seperti tenaga kesehatan, pengemudi ojek online lebih mudah terpapar akan infeksi COVID-19.…”
Section: Hasil Dan Pembahasanunclassified
“…Hal ini dapat dikarenakan karyawan yang tidak melakukan work from home (WFH) seperti tenaga kesehatan, pengemudi ojek online lebih mudah terpapar akan infeksi COVID-19. Menurut (Rahman et al, 2022) mengatakan bahwa pekerja yang bekerja dalam ruangan juga akan lebih mudah teinfeksi COVID-19 karena ruangan yang tertutup terbatas akan sirkulasi udara.…”
Section: Hasil Dan Pembahasanunclassified
“…19 p-value of 0.026 16 and the research in the Kapasa Makassar Village showed the same results, namely the level of education has a significant relationship with COVID-19 prevention behavior, meaning that a high level of education has good COVID-19 prevention behavior. 20 The results showed that some of the respondents worked. The results of the bivariate analysis showed that there was no relationship between work variables and COVID-19 prevention behavior with odds of 1.157.…”
Section: Introductionmentioning
confidence: 99%